Soils of the polar archaeological site “Settlement Labytnangi 1 (Komy village)”: morphological analysis and chemical composition - T. I. Nizamutdinov; A. R. Suleymanov; E. N. Morgun; An. V. Gusev; O. S. Tupakhina; Al. V. Gusev; A. V. Plekhanov; D. S. Tupakhin; E. V. Abakumov (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
Soils of archaeological sites are highly interesting objects for multidisciplinary research in various fields of soil science, ecology, archaeology, anthropology and other sciences. Currently, the soils of archaeological sites in the Arctic regions have not been studied sufficiently, although many ancient monuments beyond the polar circle have been found. This work is devoted to the study of morphological and chemical properties of soils of the archaeological site “Settlement Labytnangi 1”, which is located beyond the northern polar circle, near the cities of Labytnangi and Salekhard (Yamal-Nenets Autonomous Okrug). Development of these territories (according to archaeological research) began in the Eneolithic (Late IV – III millennia BC) and continues to the present day. Soil types on the territory of the monument are represented by soil-like bodies (urbikvazizems), podzols, turbozems, urbo-agrozems and peat soils with inclusions of archaeological and anthropogenic artifacts dating back to the XX century. Most of the studied soils were previously subjected to the processes of cryoturbation, although at present the lower boundary of the active layer of permafrost lies at a depth of 120–130 cm, according to the conducted electrophysical sounding. Significant changes occurred in the acid-base properties of the studied soils. In addition, anthropogenic activity entailed the introduction of biophilic elements and organic matter into the soil profile, in particular phosphorus, which is concentrated in the urbanized soil horizons (phosphorus concentrations above 2 800 mg/kg were recorded). The concentrations of heavy metals in the soils are at/below the conventional background (vicinity of Salekhard and Labytnangi). However, some excess concentrations of copper (up to 87.5 mg/kg), zinc (up to 303.3 mg/kg), lead (up to 76.1 mg/kg), and cadmium (up to 2.1 mg/kg) in the urbanized soil horizons have been detected. According to the results of the work, we can conclude that the soils of the archaeological site were formed under the strong influence of modern and past anthropogenic activity, which determined their morphological structure and chemical characteristics at present.